Lichen sclerosus in pediatric age: A new disease or unknown pathology? Experience of single centre and state of art in literature - Rossella Angotti; Giulia Fusi; Elena Coradello; Clelia Miracco; Francesco Ferrara; Marina Sica; Alessandra Taddei; Gabriele Vasta; Mario Messina; Francesco Molinaro (PAGEPress Publications, 2022)
Lichen Sclerosus (LS) is a chronic inflammatory skin disease with unknown etiology. In pediatric age the main disease "lichenlinked" is the phimosis in male. This is a retrospective study that reports the experience of our clinic and review of the literature. We included all patients affected by pathological phimosis, treated by circumcision between January 2015 and May 2020, older than 6 years old and with an histopathological diagnosis of lichen sclerosus. The aim was to identify prognostic factors based on histological report to plan the clinical management of patients. Statistical analysis was done. We included 207 patients. The mean age of children was 9,78 years (5-18 years, DS±3.29). Based on the histological features we divided patients in 2 groups: early lesions (70/207, 34%) and advanced (137/207, 66%). In term of complications lichen linked we considered meatal stenosis that needed of urethral dilatations. We included 7 patients (7/207, 3,4%). We report P value Statistical Significance in many aspects. An early diagnosis of LS and surgical treatment of foreskin are essential to prevent early and late complications in children. The size of sample is a limit of the study but results encourage our management.